Interactive Mixed Reality Museum for Ulos Batak Cultural Heritage Preservation and Global Recognition - Halim, Jasmine Meilani; Lubis, Dinda Pebriani; Hasibuan, Aziz Parham Ramadhan; Syardhi, Rizfan Dio; Ningsih, Ranti Widya; Alda, Tania (International Journal of Architecture and Urbanism, 2024)
Indonesia, with its abundant cultural riches, faces challenges in preserving the traditional Batak cloth, Ulos, which is now threatened by globalization and foreign cultural claims. Ulos, which has been designated as Indonesia's Intangible Cultural Heritage (WBTb) since October 17 2014, has not yet received international recognition from UNESCO as part of the Intangible Cultural Heritage (ICH) list. This recognition is very important to increase global awareness about Ulos and the need for its preservation. Considering these challenges, this research proposes the creation of "Ulos Heritage: Mixed Reality-based Interactive Museum" as an innovative solution to preserve and promote Ulos. This museum was designed with an interactive technology approach, using mixed reality to create a memorable and immersive experience for visitors. This approach involves presenting the collection in an appropriate atmosphere and providing a hands-on experience through augmented and virtual reality technologies. Design methods include literature studies, site surveys, and distributing questionnaires to ensure designs that suit visitor needs. This museum will be located in Medan City, North Sumatra, with facilities including an exhibition area, interactive space and souvenir area. This initiative aims to strengthen public understanding of Ulos and support global recognition as a cultural heritage that must be preserved.